2007
DOI: 10.1111/j.1468-2419.2007.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of training design, individual characteristics and work environment on transfer of training

Abstract: This study aims to gain insight into some of the factors that determine the transfer of training to the work context. The present research examined the relationship between three types of predictors on transfer of training, including training design, individual characteristics and work environment. Data was collected at two points in time from 182 employees in a large grocery organization. The results indicated that transfer design, performance self-efficacy, training retention and performance feedback were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
342
6
31

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(404 citation statements)
references
References 40 publications
(109 reference statements)
25
342
6
31
Order By: Relevance
“…Várias pesquisas, nacionais e estrangeiras, têm buscado encontrar preditores para o impacto do treinamento no nível do comportamento no cargo (Abbad et al, 2000;Freitas e Borges-Andrade, 2004;Ford et al, 1992;Lacerda, 2002;Meneses, 2002;Rowold, 2007;Tziner et al, 2007;Velada et al, 2007;Warr e Bunce, 1995). Os resultados indicam que algumas variáveis individuais ajudam a explicar a aplicação dos conhecimentos, habilidades e atitudes aprendidos nos eventos de capacitação.…”
Section: Impacto Do Treinamento No Trabalhounclassified
“…Várias pesquisas, nacionais e estrangeiras, têm buscado encontrar preditores para o impacto do treinamento no nível do comportamento no cargo (Abbad et al, 2000;Freitas e Borges-Andrade, 2004;Ford et al, 1992;Lacerda, 2002;Meneses, 2002;Rowold, 2007;Tziner et al, 2007;Velada et al, 2007;Warr e Bunce, 1995). Os resultados indicam que algumas variáveis individuais ajudam a explicar a aplicação dos conhecimentos, habilidades e atitudes aprendidos nos eventos de capacitação.…”
Section: Impacto Do Treinamento No Trabalhounclassified
“…Sin embargo, no siempre ha habido coincidencia en los resultados obtenidos por los distintos autores, así en el factor apoyo de los jefes y compañeros para transferir, algunos encuentran una relación indirecta con la transferencia (e.g., Chiaburu, Van Dam y Hutchins, 2010;Nijman et al, 2006;Schindler, 2013); y otros hablan de relación débil o incluso niegan que exista tal relación (Axtell et al, 1997;Devos et al, 2007;Nijman et al, 2006;Van der Klink, Gielen y Nauta, 2001;Velada, Caetano, Michel, Lyons y Kavanagh, 2007).…”
Section: Introductionunclassified
“…From what they found out about trainees in their study their participation of increased when they realized that the training was useful to their career. Trainees are more likely to transfer the training content to the work context when they perceive that the training program was designed and delivered in such a way that maximizes the trainee's ability to transfer the training to the job (Velada et al, 2007).…”
Section: The Contentmentioning
confidence: 99%
“…Similar to cognitive ability, Velada et al (2007) define training retention as the degree to which trainees retain the content after training is completed. Van Gerven et al (2002) in their study found out that elderly spent more time on training and experienced higher levels of cognitive load relative to the young, which strongly supported the view that working memory plays an essential role in learning new skills; and that elderly participants are disproportionally favored when studying worked examples.…”
Section: Age Of the Traineementioning
confidence: 99%